Studying the Armenian Eucharist: the vesting ritual as a case study in methodology - Shokhikyan, Arman G. (2019)
This research investigates how the Eucharistic practice of the Armenian tradition can be brought into dialogue with the historical sources and contemporary theology. The originality of this study is that it applies an interpretative vocabulary for the Armenian Eucharist outside of conventional historical-philological and theologically oriented studies. The thesis uses a holistic approach, integrating textual reading, historical theology, and ritual studies to argue that Eucharist is a historical product, a specific ritual system, and a distinctive performative event with its own textual structure that is experienced every Sunday as a lived theology. As methodological tools the thesis applies an interpretative vocabulary of ritual, performance and historical theology for study of the Armenian Eucharist.